1998
DOI: 10.1038/sj.onc.1202248
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of BRCA1 in human sporadic breast cancer; analysis of DNA methylation patterns of the putative promoter region

Abstract: Germ-line alterations of BRCA1 are responsible for about 50% of familial breast cancers. Although its biological function (s) has not yet been fully determined, it has been suggested that it may act as a tumor suppressor gene in breast and ovarian cancers. In sporadic breast cancers alterations of BRCA1 have not been detected and in vitro experiments have indicated that BRCA1 negatively regulates cellular proliferation. The present study was designed to identify and quantify, the BRCA1 mRNA levels, in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
94
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 21 publications
4
94
0
2
Order By: Relevance
“…Although the mutation rate is very low, the frequency of down regulation of ING1 in tumours is very substantial, similar to those described for BRCA1 (Thompson et al, 1995;Dobrovic and Simpfendorfer, 1997;Magdinier et al, 1998;Rice et al, 1998;Sourvinos and Spandidos, 1998) and p16 INK4A Brenner et al, 1996;Herman et al, 1995).…”
Section: Discussionsupporting
confidence: 65%
“…Although the mutation rate is very low, the frequency of down regulation of ING1 in tumours is very substantial, similar to those described for BRCA1 (Thompson et al, 1995;Dobrovic and Simpfendorfer, 1997;Magdinier et al, 1998;Rice et al, 1998;Sourvinos and Spandidos, 1998) and p16 INK4A Brenner et al, 1996;Herman et al, 1995).…”
Section: Discussionsupporting
confidence: 65%
“…On the other hand, the remaining 90% of breast cancers occur sporadically in the absence of any apparent genetic predisposition. In these nonfamilial cases, tumorigenesis is likely not due to mutation but rather to a drastic decrease of BRCA1 mRNA or protein levels (Magdinier et al, 1998;Rio et al, 1999). Multiple studies have shown a correlation between loss of BRCA1 expression and increased metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…A series of papers has also suggested that methylation of the BRCA1 promoter may be a signi®cant factor in decreasing BRCA1 expression in sporadic breast tumors, possibly through inactivation of a CREB site (Mancini et al, 1998). However, methylation can account for decreased BRCA1 expression only in a subset of sporadic breast cancer samples (Magdinier et al, 1998;Dobrovic and Simpfendorfer, 1997;Rice et al, 1998;Mancini et al, 1998;Catteau et al, 1999). Overall, these results suggest that sporadic breast cancer may result from defects in the genes regulating the BRCA1 promoter, or that transformation leads to a concomitant down regulation of BRCA1 expression.…”
Section: Introductionmentioning
confidence: 99%